Network Meta-Analysis of Different Intravenous Glucocorticoid Regimes for the Treatment of Graves’ Orbitopathy - Jia, Jun; Dong, Jingjian; Deng, Lin (Frontiers in Pharmacology, 2022)
Background: Intravenous glucocorticoid (GC) has been proposed to treat moderately severe Graves orbitopathy (GO), however the optimal regime remains debatable. We therefore performed this network meta-analysis to objectively determine the comparative efficacy and safety of different intravenous GC regimes including daily, weekly, or monthly intravenous regime for the treatment of GO. Methods: We electronically searched Medline (via PubMed), EMBASE (via OVID), and the Cochrane central register of controlled trials (CENTRAL) (via OVID) to retrieve randomized controlled trials (RCTs) investigating the comparative efficacy and safety of different intravenous GC regimes in GO patients from inception of each database to March 2021. The latest search was updated in June 2021. Risk of bias of original studies was assessed using the Cochrane Risk Bias Assessment Tool. A random-effects Bayesian network meta-analysis was conducted using the Markov chain Monte Carlo (MCMC) stimulation. Ranking probabilities of all regimes were calculated to rank all regimes. Statistical analysis was conducted using ADDIS software. Results: Total 10 studies involving 593 patients met selection criteria. Network meta-analysis suggested that weekly intravenous GC regime (WR) (response: odds ratio [OR], 4.27; 95% creditable interval [CrI], 1.82 to 11.02; clinical activity score change [CASC]: standard mean difference [SMD], -0.59; 95% CrI, -1.19 to -0.03) and monthly intravenous regime (MR) (response: OR, 6.32; 95%CrI, 1.25 to 34.96; CASC: SMD, -1.17; 95% CrI, -2.32 to -0.01) was superior to oral GC regime (OGC) for response and CASC. Meanwhile, pooled results also indicated that WR was related to the decreased risk of AEs compared with OGC (OR, 0.22; 95% CrI, 0.08 to 0.62) and daily intravenous GC regime (DR) (OR, 0.19; 95% CrI, 0.03 to 0.97). Ranking probabilities indicated that MR and WR have the relatively higher probability of becoming the best option for response, proptosis and AEs. Conclusions: Based on limited evidence, WR or MR should be preferentially prescribed to treat patients with moderately severe GO. However, more studies with large sample size should be conducted to further confirm our findings and compare WR with MR.